Exploring the Shared Use of World Heritage Sites: Residents and Domestic Tourists' Use and Perceptions of the Summer Palace in Beijing. (22nd October 2014) - Su, Ming Ming; Wall, Geoffrey
Abstract Many heritage sites are shared by tourists and local residents, who may have different motivations, preferences and experiences. These common areas offer a setting for understanding how the host and guest populations utilize, interact and perceive a heritage site. Results show that residents and domestic tourists differ in their use patterns but generally share motivations, perceptions and experiences at the Summer Palace. Use conflicts and interplay are examined in relation to their behaviours, perceptions and experiences. Practical implications are generated to inform management and planning decisions for the study site and other heritage sites shared by local users and tourists. Copyright © 2014 John Wiley & Sons, Ltd.